Implementasi Keperawatan Pada Pasien Dengan Demam Thypoid - Amirah Najmah Elvarino, Amirah Najmah Elvarino; Dewi, Debby Silvia; Gusni, Jufrika; Ajani, Anggra Trisna (Jurnal Keperawatan Medika, 2025)
According to the WHO, Indonesia reports an average of 900,000 typhoid fever cases annually, with over 20,000 deaths. In West Sumatra, cases can reach 46,142 or 1.52%. At Dr. Reksodiwiryo Padang Hospital, 795 cases and 5 deaths were recorded in 2024. This case study aims to provide nursing care for typhoid fever patients, including assessment, diagnosis, intervention, implementation, evaluation, and documentation. The study was conducted in the Agus Salim Inpatient Room from February 17–21, 2025, with one patient, Mrs. P. Data were collected through observation, interviews, physical exams, and documentation. Nursing problems identified were hyperthermia, sleep disturbances, risk of infection, and risk of nutritional deficit. Interventions included hyperthermia management, sleep support, infection prevention, and nutrition management. After 5 days of care, all problems were resolved. Typhoid fever, caused by Salmonella typhi, spreads through contaminated food and water. It is recommended that patients and families increase awareness about the causes and prevention of typhoid fever.